Organization Structure, Operation Mode and Management Mechanism in Confucius Institute of Barcelona - Bo, Gao; An, Chang; Shiru, Chang (Sinología hispánica. China Studies Review, 2016)
Focusing on the organizational system, operation mode and mechanism of Confucius Institute of Barcelona, this paper explores the successful experience, current problems and solutions of Confucius Institute of Barcelona. This study involves the issues of administration, Chinese language teaching, cultural activity, relations and integration with the local government, aiming at summarizing the successful experience of Confucius Institute of Barcelona in order to provide reference for the construction of Confucius Institutes, especially the ones in Spanish-speaking countries and further spreading the Chinese language and culture globally.